2014
DOI: 10.1007/s00382-014-2242-1
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of convection permitting climate model simulations in the representation of convective precipitation

Abstract: and 2.8 km resolutions in the representation of precipitation at sub-daily timescales, and the atmospheric conditions leading to convection. Our results show that the highest resolution of RCM simulations significantly improves the representation of both hourly intensity distribution and diurnal cycle of precipitation. In addition, at convection permitting scale the atmospheric fields related to convective precipitation show a better agreement with each other. The results imply that higher spatial resolution p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
235
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(258 citation statements)
references
References 52 publications
22
235
0
1
Order By: Relevance
“…1 shows the flat Rhine valley along the western edge of the investigation domain surrounded by the sharp orography of the Black Forest, with its two main ridges in a south-west to north-east direction. The complex terrain favours orographically induced convective precipitation, which dominates in the summer period in this region (Khodayar et Fosser et al (2015) found that CLM2.8 represents well the diurnal cycle of precipitation as well as the hourly precipitation intensities in this region and season.…”
Section: Model Simulations and Investigation Areamentioning
confidence: 99%
See 3 more Smart Citations
“…1 shows the flat Rhine valley along the western edge of the investigation domain surrounded by the sharp orography of the Black Forest, with its two main ridges in a south-west to north-east direction. The complex terrain favours orographically induced convective precipitation, which dominates in the summer period in this region (Khodayar et Fosser et al (2015) found that CLM2.8 represents well the diurnal cycle of precipitation as well as the hourly precipitation intensities in this region and season.…”
Section: Model Simulations and Investigation Areamentioning
confidence: 99%
“…Although the convection parameterisation leads to the misrepresentation of the diurnal cycle of precipitation (e.g. Brockhaus et al 2008), a parameterisation for deep convection is still necessary at 7 km as shown by Fosser et al (2015). Both CLM7 and CLM2.8 use the Tiedtke scheme for shallow convection.…”
Section: Model Simulations and Investigation Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Für kleinere Regionen in Europa gibt es bereits Klimasimulationen mit einer Auflösung von 1-3 km (Hohenegger et al 2008;Prein und Gobiet 2011;Suklitsch et al 2011;Fosser et al 2015;Ban et al 2014;Kendon et al 2014). Bei diesen Auflösungen werden dabei zum Teil klimatische Phäno-mene simuliert, für die es bisher keine Beobachtungsdaten in der entsprechenden räumlichen und zeitlichen Dichte gibt, wie man sie aber für eine systematische Bewertung benötigt (Rummukainen 2010).…”
Section: Anforderungen An Modelleunclassified